2017
DOI: 10.1038/s41598-017-09492-8
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of the CHRNB3-CHRNA6 gene cluster with nicotine dependence in the Chinese Han population

Abstract: Although numerous studies have revealed significant associations between variants in the nicotinic acetylcholine receptors (nAChR) subunits and nicotine dependence (ND), only few studies were performed in Chinese subjects. Here, we performed association and interaction analysis for 20 single nucleotide polymorphisms (SNPs) in the CHRNB3-CHRNA6 gene cluster with ND in a Chinese Han population (N = 5,055). We found nominally significant associations for all tested SNPs with ND measured by the Fagerström Test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…Nicotinic acetylcholine receptor (CHRN) genes code nAChRs, which bind to nicotinic that cause nicotinic dependence and smoking-related diseases. Recently, the associations of rs3743073 and rs667282 in CHRNA3-A5 and rs4950 in CHRNB3-A6 with tobacco consumption and lung cancer risk have been discovered [11,12,14,15]. Chronic smoking and environmental factors contribute to the development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotinic acetylcholine receptor (CHRN) genes code nAChRs, which bind to nicotinic that cause nicotinic dependence and smoking-related diseases. Recently, the associations of rs3743073 and rs667282 in CHRNA3-A5 and rs4950 in CHRNB3-A6 with tobacco consumption and lung cancer risk have been discovered [11,12,14,15]. Chronic smoking and environmental factors contribute to the development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation is the only evidence-based intervention, which can reduce the risk of developing COPD and slow down the accelerated decline of lung function in patients with COPD [21]. Nicotine dependence and smoking cessation are influenced by genetic factors [14,15,22,23]. The study of Pérez-Rubio et al [24] demonstrated that rs6313 in HTR2A increased the risk for the early onset of smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold for the genotyping rate of all SNPs was set as ≥95%, and the p value for the HWE was set as no ≥5%. All procedures and conditions used in this study were essentially the same as what we reported previously on the same samples 44 , 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Association analysis with the FTND score was performed using Haplo Stats (v. 1.7.7) 50 . For the approach used for performing haplotype-based association analysis, please refer to our previous reports 43 , 44 .…”
Section: Methodsmentioning
confidence: 99%